1997
DOI: 10.1007/s004240050458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glicentin, oxyntomodulin and related peptides on isolated gastric smooth muscle cells

Abstract: Glicentin (proglucagon 1-69 GLIC) and oxyntomodulin (proglucagon 33-69 or OXM) are two peptide hormones that are co-released from ileum and large intestine during digestion. They modulate in vivo gastric acid secretion and the gastro-pyloro-duodenal activity. The specificity of their effects is linked to the presence of their C-terminal octapepide. As yet, no isolated target cell that responds specifically to this family of peptides has been described. The present report describes the in vitro effect of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
(130 reference statements)
0
20
0
Order By: Relevance
“…A direct effect of GLP‐1 on gastric smooth muscle cells seems unlikely since the peptide changes neither the basal tone of gastric smooth muscle strips nor the length of smooth muscle cells 31,32 . Furthermore, studies in animals demonstrated that GLP‐1‐mediated effects on gastric emptying are dependent on an intact vagus nerve 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…A direct effect of GLP‐1 on gastric smooth muscle cells seems unlikely since the peptide changes neither the basal tone of gastric smooth muscle strips nor the length of smooth muscle cells 31,32 . Furthermore, studies in animals demonstrated that GLP‐1‐mediated effects on gastric emptying are dependent on an intact vagus nerve 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, OXM most likely triggered insulin secretion by simultaneous activation of GLP-1 and glucagon receptors on ␤-cells (17). However, interaction with (an)other receptor(s) cannot be excluded, because OXM was shown (38) to induce contraction of antral smooth muscle cells in an in vitro model in which GLP-1 and glucagon had no effect at all.…”
Section: Discussionmentioning
confidence: 99%
“…Oxyntomodulin was provided by Sigma (St Quentin Fallavier, France). Its biological activity tested in vitro 15 fully fitted with that obtained with natural OXM 23 . The C‐terminal fragment GLIC 51‐69 was produced using a solid‐phase synthesis procedure: its biological activity has been established 15 …”
Section: Peptidesmentioning
confidence: 74%
“…In vivo , GLIC 51‐69 has been shown to be as potent as OXM to inhibit gut secretions 7,13 . In vitro , the GLIC 51‐69 is 15 time less potent than GLIC on one target cell, which is the antral smooth muscle cell 15 . Thus, the fragment preferentially mimics the OXM effects, presumably on the vagus nerve 7 and the enteric nervous system 6 as demonstrated in rats.…”
Section: Discussionmentioning
confidence: 99%